2007
DOI: 10.1017/s002221510700059x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic tests for immunomediated hearing loss: a systematic review

Abstract: The results of diagnostic tests for immunomediated hearing loss depend on many factors, and there is a risk of potential bias. This is the first time that such a systematic review has been presented; such a review is a more rigorous method of demonstrating the utility of the available diagnostic tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The analysis of immunological parameters using specific laboratory tests was performed without obtaining conclusive results [ 5 , 11 , 23 , 38 , 39 ]. A statistically significant relationship ( p = 0.029) between SNHL diagnosed using HFA and anti-cardiolipin (aCL) positivity (OR < 1) was observed.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of immunological parameters using specific laboratory tests was performed without obtaining conclusive results [ 5 , 11 , 23 , 38 , 39 ]. A statistically significant relationship ( p = 0.029) between SNHL diagnosed using HFA and anti-cardiolipin (aCL) positivity (OR < 1) was observed.…”
Section: Resultsmentioning
confidence: 99%
“…A recent systematic review of the diagnostic tests used for autoimmune hearing loss revealed significant heterogeneity and a lack of standardization across the literature. 35 The relevant studies in this review were able to identify significant elevations in nonspecific inflammatory markers and identify significant changes in autoantibodies and cellular changes in SSNHL patients. 2,16,18 None of the studies were able to identify an inflammatory marker specific for autoimmune inner ear disease, as all of the reviewed studies' findings have been previously associated with other systemic inflammatory diseases.…”
Section: Autoimmune Diseasementioning
confidence: 95%
“…In certain cases, serological studies can detect some specific autoantibodies, but there are no immunological or serological tests that are specific or sensitive enough to establish a definitive diagnosis [18] . A summary of the main specific and non-specific autoantibodies found in AIED patients and experimental models is given in Table 1.…”
Section: Diagnosismentioning
confidence: 99%